PTH-121 Transarterial chemoembolisation at king's – a comparison of conventional tace vs tace with beads in clinical practice. (22nd June 2015) - Pennycuick, A; McPhail, M; Considine, A; O'Grady, N. Heaton, J; Suddle, A
Abstract : Introduction: Trans-arterial chemoembolisation (TACE) is a well established treatment modality for hepatocellular carcinoma (HCC). Recently our standard of care has changed from conventional doxyrubicin TACE (cTACE) to TACE using doxyrubicin eluting beads (TACE-DEB). Evidence has shown equivalent efficacy with reduced side effects. We analysed TACE procedures during this transition to determine impact on clinical outcomes. Method: We reviewed the records of 152 TACE procedures performed between April 2013 and January 2014 from our electronic patient record. Demographic, treatment, length of stay and mortality data were collated and analysed for length of stay and subsequent mortality. Multivariate analysis was performed using a Cox model. Results: We analysed data from 152 TACE procedures (92 cTACE, 60 TACE-DEB) performed on 109 patients between April 2013 and January 2014. The groups were matched in terms of age, sex, aetiology of underlying liver disease and baseline biochemistry. Length of stay was significantly less with TACE-DEB (mean 2.33 days, SD 1.03) compared to cTACE (mean 2.56 days, SD 1.04); p = 0.045. There was no difference in mortality (p = 0.75). Increased mortality was associated with baseline Child-Pugh score (p = 0.019), MELD (p = 0.008), albumin (p = 0.008), ALP (p = 0.046) and neutrophil count (p = 0.029). Mortality was significantly higher if baseline bilirubin > 30 (p = 0.007), creatinine > 100 (p = 0.0297) or albumin < 30 (p = 0.008). On multivariate analysis only albumin was an independent predictor of mortality (p = 0.027). Conclusion: TACE-DEB significantly reduced length of stay compared to cTACE in our cohort. Low albumin was the best independent predictor of mortality and is independent of TACE modality. These data help inform relative contraindications for this procedure. Disclosure of interest: None Declared.